Social capital and life satisfaction: a cross-sectional study on persons with musculoskeletal impairments in Hanoi, Vietnam - Jimba Masamine; Sakisaka Kayako; Poudel Krishna C; Thuy Nguyen; Takahashi Kyo; Yasuoka Junko (BMC, 2011)
Abstract Background Social capital has been recognized as a major social determinant of health, but less attention has been given to social capital of persons with musculoskeletal impairments. The present study aimed to explore the associations between social capital and life satisfaction of persons with musculoskeletal impairments in Hanoi, Vietnam. Methods A cross-sectional study was conducted in Hanoi, Vietnam. From June to July 2008, we collected data from 136 persons with musculoskeletal impairments who belonged to disabled people's groups. Social capital was measured using a short version of the Adapted Social Capital Assessment Tool that included group membership, support from groups, support from individuals, citizenship activities, and cognitive social capital. Life satisfaction was measured using the Satisfaction with Life Scale. As possible confounding factors, we measured socio-economic factors and disability-related factors such as activities of daily living. Results After controlling for confounding effects, group membership remained significantly associated with the level of life satisfaction reported by the persons with musculoskeletal impairments. In particular, being an active member of two or more groups was associated with higher life satisfaction. In contrast, other components of social capital such as citizenship activities and cognitive social capital were not significant in the multiple regression analysis of this study. Conclusions The findings suggest the importance of considering an active participation in multiple groups toward the enhancement of the life satisfaction among persons with musculoskeletal impairments. To encourage persons with musculoskeletal impairments to have multiple active memberships, their access to groups should be facilitated and enhanced.